Shifts and sensationalism in press coverage of drought in the territory of Slovenia (1921–2003) - Osojnik, Janez (Studia Historica Slovenica, 2025)
This article examines how major droughts that affected all or parts of the Slovenian ethnic territory between 1921 and 2003 were reported in major Slovenian daily newspapers. Using qualitative content analysis, supported by basic corpus techniques, it analyses coverage of eight drought years (1921, 1939, 1950, 1952, 1962, 1983, 1992, and 2003) in Slovenec, Slovenski narod, Jutro, Slovenski poročevalec, Ljudska pravica, Delo, and Večer. The article analyses which vocabulary and metaphors newspapers used to describe heat and drought, how they reported on the impacts on agriculture and water resources, and how they portrayed state authorities, expert institutions, and farmers both as key response actors and as those most severely affected by the consequences of drought. It shows a shift from locally grounded and often sensational narratives in the interwar period, through more restrained and regime-aligned reporting under socialism, to more critical and risk-oriented framings after independence.
Keywords: 20. st.; 20th cent.; 21. st.; 21st. cent.; climate changes; časniško poročanje; drought; environmental history; heat; okoljska zgodovina; podnebne spremembe; press coverage; Slovenia; Slovenija; suša; vročina